Launching A Digital Mental Health Dictionary in Indonesian Sign Language to Enhance Mental Health Information Accessibility for The Deaf Community - Rivo Mario Warouw Lintuuran; Laura Lesmana Wijaya; Rodhiyah Rodhiyah; Adhesatya Ningsih Moodoeto (Devotion : Journal of Research and Community Service, 2026)
Communication barriers remain a major obstacle to accessing mental health information and services among Deaf individuals. The limited availability of mental health terminology in Bahasa Isyarat Indonesia (BISINDO) can hinder communication between Deaf individuals, sign language interpreters, and mental health professionals. This community service program aimed to introduce and disseminate a digital BISINDO mental health dictionary as an accessible resource for mental health education and communication. A one-day community engagement program was conducted involving Deaf community members, sign language interpreters, mental health professionals, students, and government representatives. The program included presentations on the need for a mental health dictionary, the dictionary development process incorporating 80 terminologies, demonstrations of BISINDO mental health terminology through YouTube videos, a talk show featuring a psychiatrist and a clinical psychologist from Mental Health Deaf Indonesia, and an interactive question-and-answer session. Program evaluation was based on participant feedback. Participants expressed positive responses regarding the relevance of the dictionary, the free accessibility of video-based content, and its potential use in mental health education and service settings. Feedback highlighted the importance of standardized mental health terminology in BISINDO and the value of collaboration between Deaf and hearing professionals. The digital BISINDO mental health dictionary shows promise as an accessible communication and educational resource that may support more inclusive mental health services for Deaf communities.